2021
DOI: 10.1371/journal.pone.0254817
|View full text |Cite|
|
Sign up to set email alerts
|

Percutaneous hepatic melphalan perfusion: Single center experience of procedural characteristics, hemodynamic response, complications, and postoperative recovery

Abstract: Background Percutaneous hepatic melphalan perfusion (PHMP) for the selective treatment of hepatic metastases is known to be associated with procedural hypotension and coagulation disorders. Studies on anesthetic management, perioperative course, complications, and postoperative recovery in the intensive care unit (ICU) have not been published. Methods In a retrospective observational study, we analyzed consecutive patients who were admitted for PHMP over a 6-year period (2016–2021). Analyses included demogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
23

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(39 citation statements)
references
References 19 publications
1
15
0
23
Order By: Relevance
“…Therefore, high doses of melphalan can be administered while minimizing systemic side effects [ 1 , 2 ]. In the past years the feasibility and repeatability of CS-PHP in the setting of unresectable hepatic metastasis has been shown in numerous studies [ 2 9 ]. Especially in unresectable liver metastases of uveal melanomas CS-PHP has proven to be an effective and save therapeutic option [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, high doses of melphalan can be administered while minimizing systemic side effects [ 1 , 2 ]. In the past years the feasibility and repeatability of CS-PHP in the setting of unresectable hepatic metastasis has been shown in numerous studies [ 2 9 ]. Especially in unresectable liver metastases of uveal melanomas CS-PHP has proven to be an effective and save therapeutic option [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…All procedures were performed under general anesthesia due to the length of the procedure and hemodynamic changes that occur with the extracorporeal hemofiltration circuit and inferior caval vein occlusion [ 25 ]. The first day after the PHP, patients received a single shot of antibiotics as well as granulocyte colony-stimulating factor (G-CSF).…”
Section: Methodsmentioning
confidence: 99%
“…The rate of clinically relevant hyperbilirubinemia is reported to be up to 15 % and appears to correlate with tumor burden [13]. A recent study showed that the side effect spectrum does not change even with repeated sessions (up to six) [5], other data show that up to eight repetitions are possible [4]. Ultimately, the majority of reported adverse events were transient in nature or manageable, and treatment-associated deaths occurred very rarely (< 1 %) in the published cohorts (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15).…”
Section: Range Of Side Effectsmentioning
confidence: 99%
“…In einer aktuellen Studie konnte gezeigt werden, dass sich das Nebenwirkungspektrum auch bei wiederholten Sitzungen (bis zu 6) nicht ändert [5], andere Daten zeigen, dass bis zu 8 Wiederholungen möglich sind [4]. Letztlich war die Mehrheit der berichteten Nebenwirkungen von transienter Natur bzw.…”
Section: Patientensicherheitunclassified
See 1 more Smart Citation